PHATIC PARTICLES IN PRESIDENTIAL CANDIDATE DEBATE ACTIVITIESAND CANDIDATE FOR VICE-PRESIDENT OF THE REPUBLIC OF INDONESIA IN 2024 - Shinta Amelia Putri; Lindawati; Nadra (Lire Journal (Journal of Linguistics and Literature), 2025)
This study aims to describe phatic particles and their functions found in the debate of presidential and vice-presidential candidates of the Republic of Indonesia in 2024. This type of research is descriptive qualitative. The data collection method used is the listening method with the basic technique of tapping, then the advanced technique is listening freely involving conversation. After that, the data was analyzed using the distribution method with the basic technique for direct elements. From the analysis that has been carried out, ten types of phatic particles were found that were used in the 2024 RI presidential and vice-presidential candidate debate. Then, the function of phatic particles found in the 2024 RI presidential and vice presidential candidate debate is as a substitute for words only, a substitute for words too, to emphasize or highlight a part, as a transition in conversation, or to show emphasis on new information, substitute for the words not and isn't, emphasize proof, emphasize imperative sentences, confirm or reinforce a statement, strengthen the title, emphasize the reason, emphasize the denial, emphasize the surprise, replace the question words why or why not, emphasize a warning, and indicate something specifically, as the true or actual meaning, refines the command, and to force by persuading. Overall, the use of phatic particles helps maintain smooth communication, makes debate events more interactive and effective, and shows participants' strategies in conveying arguments clearly and persuasively.